Pemberian Tepung Kulit Pisang Terfermentasi Dalam Ransum Terhadap Recahan Karkas Ayam Kampung Super - I Made Artama; Ni Ketut Etty Suwitari; I Gusti Ayu Dewi Seri Rejeki (Fakultas Pertanian, Universitas Warmadewa, 2022)
The purpose of this study was to determine the effect of fermented banana peel flour in the ration on the carcass of super native chickens aged 10 weeks. And knowing what percentage of the level of fermented banana peel flour in the ration was able to give the best results to the carcass fragments of super native chickens aged 10 weeks. The research design used was a completely randomized design (CRD) which consisted of 5 treatments, namely: R0 (ration without fermented banana peel flour), R1 (ration with 2.5% fermented banana peel flour), R2 (ration with 5% banana peel flour). fermented banana), R3 (ration with 7.5% fermented banana peel flour), R4 (ration with 10% fermented banana peel flour). Provision of fermented banana peel flour in the ration had no significant effect (P>0.05) on carcass weight, thigh weight, chest weight, back weight and wing weight